Teacher Well-Being in EFL/ESL Classrooms - Li, Zhong (Frontiers in Psychology, 2021)
A popular point in the last twenty years in academic and business settings is well-being at work that is in line with positive psychology, through which one can understand how to make working conditions enjoyable. Alternatively, teaching has been recognized as the most stressful career. Notwithstanding, not many studies in the form of review have been carried out to focus on the notion of teachers’ well-being in English as a second language (ESL) or English as a foreign language (EFL). According to the literature review, the definition of this construct, factors related to it, and empirical studies in this domain are presented. In conclusion, the implications of well-being for teachers, school principals, teacher-trainers, and future researchers are provided, and new directions for future research are delineated.